Economic efficiency of US 2007 heavy-duty diesel emission standards: a lifecycle-based approach - Anderson, Aaron, author; Kling, Robert W., advisor; Willson, Bryan D., committee member; Iverson, Terrence W., committee member; Bernasek, Alexandra, committee member (Colorado State University. Libraries, 2010)
A new method of evaluating vehicle emission standards is developed and applied to US 2007 heavy-duty diesel emission standards. The method is closely related to lifecycle analyses because it relies on the calculation of lifecycle costs of a single vehicle meeting the new standards, as well as the lifecycle costs of a vehicle compliant with previous standards. This allows the calculation of a per-vehicle net benefit, which is then, along with forecasted vehicle sales, used to estimate the total net benefit of the standards imposed over some period of years. There are multiple advantages to the approach developed here relative to that used by the EPA. Primarily, it allows a comparison of benefits and costs that occur across different periods of time, it relies on marginal damage estimates from the peer-reviewed literature, and it is easily adaptable to different emission standards. In contrast to the result of the EPA analysis, it is found that the net benefit of the standards is negative.
Keywords: truck; standards; externalities; emissions; diesel; benefit-cost; Diesel trucks -- United States -- Cost of operation -- Evaluation; Diesel motor exhaust gas -- United States -- Measurement; Air -- Pollution -- Standards -- United States; Life cycle costing